Refractory thrombocytopenia after 177Lu-PSMA therapy: bone marrow infiltration (myelophthisis) versus treatment toxicity - Camadan, Yasemin Aydinalp; Bayram, Ertugrul; Toyran, Tugba; Köseci, Tolga; Guney, Isa Burak; Kara, Ismail Oguz; Sahin, Berksoy (Scientific Reports in Medicine, 2026)
Lutetium is a radiopharmaceutical used effectively to treat metastatic castration-resistant prostate cancer (mCRPC). Myelosuppression can occur after lutetium therapy, and it can be difficult to distinguish between treatment-related toxicity and bone marrow infiltration (myelophthisis), especially in patients with extensive bone metastases. A 60-year-old male patient with metastatic castration-resistant prostate cancer was scheduled for 177Lu-PSMA therapy after progression on docetaxel and abiraterone. Thrombocytopenia developed after the first course. At the same time, the patient developed infective endocarditis. Although platelet counts temporarily improved with infection management, severe thrombocytopenia recurred after the second 177Lu-PSMA cycle. Bone marrow biopsy revealed infiltration by prostate adenocarcinoma. It was determined that the patient’s thrombocytopenia was caused by cancer infiltration of the bone marrow and the resulting myelophthisis. Hematologic toxicity is a recognized complication of 177Lu-PSMA therapy in patients with mCRPC and extensive skeletal involvement, bone marrow is essential to differentiate between effects caused by treatment and myelophthisis in cases of refractory cytopenia.